An integrated communications platform incorporating SMS and e–mail to support mobile applications. (29th December 2014) - Elton, James; Chung, Paul W.H.
The popularity and ubiquity of mobile communication devices has allowed people in a mobile society to communicate in almost any location. In this article a novel platform is described which provides a framework for supporting multiple communication services, including short message service and electronic mail. This platform has a generic architecture to facilitate the inclusion of a range of different application scenarios in a mobile environment. Each scenario represents a problem or an event, whereby the platform can interact with, and utilise, mobile phone and tablet users in this mobile society to attempt to solve the aims of the scenario. Implemented within the platform is a data analysis procedure to process and respond to information received from users autonomously. An example scenario aimed at tracking missing persons is described with the objective of evaluating the functionality of the platform's architecture.